Das estrategias aos danos : estudos de efeitos socioambientais da instalação de gasoduto Gavião Branco na comunidade Bom Jesus dos Pretos - Silva, Jessica Maria Barros da (2016)
This study presents the description of a social situation experienced by the community of Bom Jesus dos Pretos, seat of the quilombo territory of the same name, located in White Hawk pipeline affectation area. In an overview, outline the passage between the arrival of the company and its strategies and the state of discourse in order to promote an approach that contextualizes the ―Lexos " business development which reinforced the image from gas holdings in the territory. Demonstrate through narratives and documentation, the changes that installation on the Community reality of Maroons before the emergence of social and environmental impacts from the beginning of the activities of Parnaíba Gás Natural company. Dialogue to this, the mobilizations of Quilombo with the completion of the procedures of environmental impact assessment , ( which are integral , permitting the public hearings , reporting ) , the actions taken by the company as a way to mitigate the consequences of passage of pipes amid anthropic area of Bom Jesus dos Pretos , which includes this perspective the preparation of materials such as Basic Environmental Plan and building a "social mapping "